2015
DOI: 10.1073/pnas.1510540112
|View full text |Cite
|
Sign up to set email alerts
|

Neofunction of ACVR1 in fibrodysplasia ossificans progressiva

Abstract: Fibrodysplasia ossificans progressiva (FOP) is a rare genetic disease characterized by extraskeletal bone formation through endochondral ossification. FOP patients harbor point mutations in ACVR1 (also known as ALK2), a type I receptor for bone morphogenetic protein (BMP). Two mechanisms of mutated ACVR1 (FOP-ACVR1) have been proposed: ligand-independent constitutive activity and liganddependent hyperactivity in BMP signaling. Here, by using FOP patient-derived induced pluripotent stem cells (FOP-iPSCs), we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
339
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(372 citation statements)
references
References 45 publications
(88 reference statements)
17
339
2
Order By: Relevance
“…Using a new mouse model fully recapitulating the phenotype of the disease, that is, spontaneous induced HO mediated by altered BMP signaling, the authors demonstrated that activin A is capable of inducing Smad 1/5/8 phosphorylation and downstream transcriptional activation exclusively in the presence of the mutant ALK2 receptor. This finding was confirmed shortly thereafter by an independent group (14). Although this message probably summarizes the major translational finding, there is other relevant information provided within the manuscript.…”
Section: Alk2 Becomes Promiscuoussupporting
confidence: 59%
See 1 more Smart Citation
“…Using a new mouse model fully recapitulating the phenotype of the disease, that is, spontaneous induced HO mediated by altered BMP signaling, the authors demonstrated that activin A is capable of inducing Smad 1/5/8 phosphorylation and downstream transcriptional activation exclusively in the presence of the mutant ALK2 receptor. This finding was confirmed shortly thereafter by an independent group (14). Although this message probably summarizes the major translational finding, there is other relevant information provided within the manuscript.…”
Section: Alk2 Becomes Promiscuoussupporting
confidence: 59%
“…These are secreted antagonists characterized by an activin binding site, although they can also interact with other ligands of the TGF-β family (23). Indeed, Hino et al tested a number of follistatin-like proteins to prevent activin A induced chondrogenesis in FOP iPSCs-derived MSCs (14). Finally, mutual antagonism is usually observed between members of the TGF-β family, by means of competing for the same receptors at the membrane or intracellular regulators that mediate gene transcription (24).…”
Section: Anti-activin Based Therapies For Fopmentioning
confidence: 99%
“…The efficacy of palovarotene is currently tested in a phase II clinical trial (ClinicalTrials.gov, NCT02190747). Moreover, a monoclonal antibody against activin A was reported to impair HO in a mouse model and in iPS cells with the FOP mutation (Hatsell et al 2015;Hino et al 2015); although the cellular mechanism for this mode of action has not been determined, the data suggest that activin A may be a therapeutic target for FOP.…”
Section: Heterotopic Ossification Caused By Dysregulation Of Bmp Signmentioning
confidence: 99%
“…As suggested by previous in vitro studies, these mutations have a "gain of function" effect on the receptor's activity with dysregulation of the downstream pathway and increased responsivity to BMPs (6,(9)(10)(11)(12). Very recently, two seminal works have demonstrated that these mutations cause a modification of ACVR1 ligand binding properties, by conferring to the mutated receptor the ability to respond to Activin-A, a molecule that normally transduces TGF-b signaling through the Smad2/3 cascade (13,14). In FOP, the binding of Activin A to the mutated receptor, improperly induces the activation of the canonical, ACVR1-mediated, Smad1/5/8 pathway thus committing resident, tissue-specific, multipotent progenitors to the formation of ectopic bone (15).…”
Section: Introductionmentioning
confidence: 96%